Efficacy of compost tea on Septoria leaf spot of tomato in field and greenhouse studies - Bates, Marlin A (Kansas State University, 2007)
With acceptance and utilization of chemical pesticides declining, some vegetable producers are turning to alternative methods to manage plant health issues. Compost tea (CT) has provided control of some foliar pathogens and may provide benefits beyond disease suppression. Despite an increasing body of popular and scientific literature focusing on CT as a biological control option for growers, information on the efficacy of CT is still lacking for many pathosystems. In this study, field trials were conducted to evaluate the efficacy of CT on Septoria lycopersici, causal agent of Septoria leaf spot on tomato, in Kansas, in 2006 and 2007. Previous research done at KSU with a similar CT showed adequate control of this pathogen in field and greenhouse studies conducted. Additional work to develop a rapid screening method for efficacy of CT formulations was carried out in the greenhouse at Manhattan, KS. CT sprayed weekly on tomato plants prior to and after disease onset led to no significant difference in control of the pathogen compared to untreated controls. A contact fungicide (chlorothalonil) provided significant control of the pathogen in 2007, but not in 2006. These results contrast with those obtained in previous K-State research. It is difficult to assess why such striking differences were obtained, but the variation in these results point to the need to identify optimal recipes of CT for this pathosystem. Preliminary investigations standardized plant age, inoculum concentration, incubation conditions, and incubation interval for measurable Septoria leaf spot disease development on young tomato plants in the greenhouse. Ingredients of the field-tested CT were used to make a variety of CTs to test using the greenhouse-screening assay. Further work on identifying effective CT recipes is needed to substantiate the validity of this screening protocol and to evaluate the correlation of this method with disease suppression in the field.
Keywords: Compost tea; Septoria lycopersici; Agriculture, Food Science and Technology (0359); Agriculture, Plant Pathology (0480)